2018
DOI: 10.1080/21640629.2018.1429113
|View full text |Cite
|
Sign up to set email alerts
|

Carefully supporting autonomy – learning coaching lessons and advancing theory from women’s netball in England

Abstract: Carefully supporting autonomy-learning coaching lessons and advancing theory from women's netball in England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…This research demonstrates how autonomous exercise motives can influence more than behaviour adherence. Indeed, as previously mentioned Cronin et al, (2018) found an autonomy supportive environment to be a key factor in engaging females in a netball program. More specifically, those who were given choice and were allowed to contribute to the netball sessions reported high levels of engagement.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…This research demonstrates how autonomous exercise motives can influence more than behaviour adherence. Indeed, as previously mentioned Cronin et al, (2018) found an autonomy supportive environment to be a key factor in engaging females in a netball program. More specifically, those who were given choice and were allowed to contribute to the netball sessions reported high levels of engagement.…”
mentioning
confidence: 73%
“…Within female orientated sport and physical activity research, the Self Determination Theory has played a key underpinning theory to explain and understand how autonomy, relatedness and competence (Cronin et al, 2018;Walsh et al, 2018;Nicholas et al, 2018) are key drivers of participation. Within this study what has become apparent is that the nature of the activity in addition to the coach's behaviours are both equally important in the motivation to engage female participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations